2014
DOI: 10.4085/1062-6050-49.2.07
|View full text |Cite
|
Sign up to set email alerts
|

Joint Stability Characteristics of the Ankle Complex After Lateral Ligamentous Injury, Part I: A Laboratory Comparison Using Arthrometric Measurement

Abstract: . Dr Liu is currently at the School of Kinesiology, Auburn University, AL. Context:The mechanical property of stiffness may be important to investigating how lateral ankle ligament injury affects the behavior of the viscoelastic properties of the ankle complex. A better understanding of injury effects on tissue elastic characteristics in relation to joint laxity could be obtained from cadaveric study.Objective: To biomechanically determine the laxity and stiffness characteristics of the cadaver ankle complex b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 21 publications
1
18
1
Order By: Relevance
“…This finding can be attributed to the quasi‐static weight‐bearing methods used in previous studies, which did not create dynamic plantar‐flexed foot position. Anterior talofibular ligament injury causes an increased anterior translation in the tibiotalar joint . Neither excessive tibiotalar anterior translation nor external/internal rotation hypermobility was detected in the current study.…”
Section: Discussioncontrasting
confidence: 71%
“…This finding can be attributed to the quasi‐static weight‐bearing methods used in previous studies, which did not create dynamic plantar‐flexed foot position. Anterior talofibular ligament injury causes an increased anterior translation in the tibiotalar joint . Neither excessive tibiotalar anterior translation nor external/internal rotation hypermobility was detected in the current study.…”
Section: Discussioncontrasting
confidence: 71%
“…This ankle arthrometer has previously been used to quantify the diagnostic validity of different subgroups in subjects or patients with CAI (Lohrer et al, 2015). Specifically, at low levels of force application deformation or stiffness measures are known to best distinguish between the tibiotalar translation and the rigidity of the ankle and its encompassing soft tissues with the talus already anteriorly translated to its end position (Kovaleski et al, 2014;Nauck et al, 2010;Tohyama et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Force as well as anterior translation were measured with embedded sensors at a frequency of 100 Hz. Previous research indicates that ankle instability can best be differentiated at low levels of force application . The very early phase of force application below 20 N was not considered for data analysis, because it is suggested that in this range rather a soft‐tissue compression would be measured than a ligamentous contribution to joint stability .…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, already in the 1980 researchers could show that sectioning the ATFL in cadavers increased the anterior translation of the ankle . Further studies could replicate these results and identify that only a relatively low amount of force is needed to elicit differences between intact and sectioned ligament conditions …”
mentioning
confidence: 94%